"Keep your feet on the ground": Simulated range of motion and hind foot posture of the Middle Jurassic sauropod Rhoetosaurus brownei and its implications for sauropod biology. (9th April 2019) - Jannel, Andréas; Nair, Jay P.; Panagiotopoulou, Olga; Romilio, Anthony; Salisbury, Steven W.
Abstract: The biomechanics of the sauropod dinosaur pes is poorly understood, particularly among the earliest members of the group. To date, reasonably complete and articulated pedes in Early Middle Jurassic sauropods are rare, limited to a handful of taxa. Of these, Rhoetosaurus brownei, from eastern Australia, is currently the only one from the Gondwanan Middle Jurassic that preserves an articulated pes. Using Rhoetosaurus brownei as a case exemplar, we assessed its paleobiomechanical capabilities and pedal posture. Physical and virtual manipulations of the pedal elements were undertaken to evaluate the range of motion between the pedal joints, under both bone‐to‐bone and cartilaginous scenarios. Using the results as constraints, virtual reconstructions of all possible pedal postures were generated. We show that Rhoetosaurus brownei was capable of significant digital mobility at the osteological metatarsophalangeal and distal interphalangeal joints. We assume these movements would have been restricted by soft tissue in life but that their presence would have helped in the support of the animal. Further insights based on anatomy and theoretical mechanical constraints restricted the skeletal postures to a range encompassing digitigrade to subunguligrade stances. The approach was extended to additional sauropodomorph pedes, and some validation was provided via the bone data of an African elephant pes. Based on the resulting pedal configurations, the in‐life plantar surface of the sauropod pes is inferred to extend caudally from the digits, with a soft tissue pad supporting the elevated metatarsus. The plantar pad is inferred to play a role in the reduction of biomechanical stresses, and to aid in support and locomotion. A pedal pad may have been a key biomechanical innovation in early sauropods, ultimately resulting in a functionally plantigrade pes, which may have arisen during the Early to Middle Jurassic. Further mechanical studies are ultimately required to permit validation of this long‐standing hypothesis. Abstract : Sauropods were iconic colossal terrestrial animals during Mesozoic times. In recent decades an emerging picture of how they operated has been developed, but many aspects of their paleobiology still remain unclear. Here, we quantify how they may have kept their hind feet on the ground. Using various conventional and computational methods, we assessed the range of motion in the digits of the hind foot of Rhoetosaurus brownei, a Middle Jurassic sauropod from Australia, to establish a gamut of potential foot postures. With additional input of biomechanical principles we ultimately delimit these to a predictable in‐life posture. We found that the foot exhibited greater flexibility than previously inferred. The hindfoot of Rhoetosaurus brownei was determined to be "skeletally digitigrade, " implying the animal walked with its phalanges in a "high‐heeled" fashion. However, the posture was almost certainly "functionally plantigrade, " meaning the animal actually impressed the full bottom surface of its foot, by virtue of an inferred cushioning pad. The soft tissue pad appears to be a key biomechanical innovation, suggested to have arisen in sauropods during the Early to Middle Jurassic.